Pantograph and Catenary Arc under Stiff Contact Wires of 120 km/h Metro Vehicles - ZHOU Dalin; GAO Wei; ZHENG Xuan (机车电传动)
Aiming at the 120 km/h vehicles pantograph and catenary arc of Guangzhou metro line 3 north-extension section, thearc generation cause was analyzed, and the pantograph and catenary model was built. With the simulation from the pantograph and thecatenary, the pantograph and catenary parameters for 120 km/h vehicles operation were provided. The test validated the good effects.